2008
DOI: 10.1021/jm801128g
|View full text |Cite
|
Sign up to set email alerts
|

Non-Peptide Macrocyclic Histone Deacetylase Inhibitors

Abstract: Inhibition of Histone Deacetylases inhibitors (HDACi) hold great promise in cancer therapy due to their demonstrated ability to arrest proliferation of nearly all transformed cell types. Of the several structurally distinct small molecules HDACi reported, macrocyclic depsipeptides have the most complex recognition cap-group moieties and present an excellent opportunity for the modulation of the biological activities of HDACi. Unfortunately, the structure-activity relationship (SAR) studies for this class of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 43 publications
2
75
0
Order By: Relevance
“…Discovery of a new class of macrocyclic histone deacetylase inhibitors (HDACi) based on macrolide antibiotics skeletons (73) was reported by Oyelere et al [137] SAR studies revealed that these compounds displayed both linker-lengthand macrolide-type-dependent HDAC inhibition activities with IC 50 in the nanomolar range. These nonpeptide macrocyclic HDACi were also found to be more selective against HDACs 1 and 2 relative to HDAC 8.…”
Section: Antifungal and Antibacterialsmentioning
confidence: 99%
“…Discovery of a new class of macrocyclic histone deacetylase inhibitors (HDACi) based on macrolide antibiotics skeletons (73) was reported by Oyelere et al [137] SAR studies revealed that these compounds displayed both linker-lengthand macrolide-type-dependent HDAC inhibition activities with IC 50 in the nanomolar range. These nonpeptide macrocyclic HDACi were also found to be more selective against HDACs 1 and 2 relative to HDAC 8.…”
Section: Antifungal and Antibacterialsmentioning
confidence: 99%
“…However, the exact relationship between zinc chelation, protein acetylation state, and splicing inhibition is not clear, as only a limited set of HDAC inhibitors (HDACis) was screened. In the present work, we sought to clarify this relationship by screening a HDACi library that was structurally more diverse (Chen et al 2008;Canzoneri et al 2009;Oyelere et al 2009;Mwakwari et al 2010a,b;Patil et al 2010). We report here the elucidation of unique molecular features that confer splicing inhibition upon zinc-chelating agents with HDAC inhibition activity.…”
Section: Introductionmentioning
confidence: 92%
“…To this end, we first screened a small (63-member), yet structurally diverse HDACi library (see Supplemental Table S1 for the structures) at 100 mM using a conventional in vitro splicing assay. The HDAC inhibition activity of compounds in the screened library against HDAC1 and HeLa cell nuclear extract HDACs ranges from single digit-to mid-nanomolar (Chen et al 2008;Canzoneri et al 2009;Oyelere et al 2009;Mwakwari et al 2010a;Patil et al 2010). Despite their potency, these HDACis did not broadly inhibit splicing.…”
Section: Screening Of Structurally Diverse Hdacis For Splicing Inhibimentioning
confidence: 99%
See 1 more Smart Citation
“…Antibacterial macrolides have attracted considerable attention for two main reasons: (a) the emergence of atypical and/or new pathogens and extensive clinical application of these antibiotics had resulted in an increasing emergence of bacterial resistance, especially among macrolideresistant Streptococcus pneumoniae, Streptococcus pyogenes, and Staphylococcus aureus strains, and, therefore, the development of alternative antibacterial agents became essential; (b) macrolide derivatives, especially 14-and 15-membered classes, have also become interesting for treating important chronic diseases, that is, asthma, chronic sinusitis, diffuse panbronchiolitis, cystic fibrosis (Čulić, 2001;Labro, 2000;Labro, 2004), bronchiolitis obliterans syndrome (BOS) (Vanaudenaerde et al, 2008;Culic et al, 2006), etc. Some macrolides proved active in treatment of malaria Kuschner et al, 1994;Andersen et al, 1995;Ohrt et al, 2002;Sidhu et al, 2007) and cancer (Romano et al, 2004;Oyelere et al 2009;Mwakwari et al 2010;Bao et al, 2010), showed antiparasitic activity (Lee et al 2011) or act as motilides, ie. macrolides with gastrointestinal motor stimulating activity (Takanashi et al 2009).…”
Section: Introductionmentioning
confidence: 99%